Volume-dependent hemodynamic effects of blood collection in canine donors - evaluation of 13% and 15% of total blood volume depletion - FERREIRA,RUI R.F. (2015)
Background: There is no consensus regarding the blood volume that could be safely donated by dogs, ranging from 11 to 25% of its total blood volume (TBV). No previous studies evaluated sedated donors.Aim: To evaluate the hemodynamic effects of blood collection from sedated and non-sedated dogs and to understand if such effects were volume-dependent.Materials and Methods: Fifty three donations of 13% of TBV and 20 donations of 15% TBV were performed in dogs sedated with diazepam and ketamine. Additionally, a total of 30 collections of 13% TBV and 20 collections of 15% TBV were performed in non-sedated dogs. Non-invasive arterial blood pressures and pulse rates were registered before and 15 min after donation. Results: Post-donation pulse rates increased significantly in both sedated groups, with higher differences in the 15% TBV collections. Systolic arterial pressures decreased significantly in these groups, while diastolic pressures increased significantly in 13% TBV donations. Non-sedated groups revealed a slight, but significant, SBP decrease. No clinical signs related to donations were registered.Conclusion: These results suggest that the collection of 15% TBV in sedated donors induces hemodynamic variations that may compromise the harmlessness of the procedure, while it seems to be a safe procedure in non-sedated dogs.